THU0555 Idiopathic Granulomatous Mastitis; A New Autoimmune Disease. (9th June 2015) - Sanint, J.M.; Olive, A.; Rodriguez, S.; Prior, A.; Julian, J.F.; Mariscal, A.
Abstract : Background: Idiopathic Granulomatous Mastitis (IGM) is a rare benign inflammatory breast disease. It presents as a painful breast mass in young women. The histologic presence of non caseating granulomas confined within breast lobules together with negative microbiologic finding, including mycobacteria and fungal cultures often confirms diagnosis. Its etiology and pathogenesis remains a subject for debate. It poses a problem of differential diagnosis because it clinically resembles other forms of mastitis and, most importantly, carcinomatous mastitis Objectives: The purpose of this work is to study epidemiology, clinical and paraclinical characteristics, pathological anatomy features and treatment of IGM. Methods: Retrospective review of clinical and radiological data of 7 women with confirmed IGM diagnosed between 2008 and 2014 in a university hospital with a catchment area of 850, 000 inhabitants diagnosis Results: 7 patients were diagnosed with IGM. Average age at diagnosis of 37.6 years (range: 29-46). Three of them were multiparous. Mean follow-up was one year; one patient did not attend clinical control. Patients were of multiethnic origin: 3 (42.8%) Caucasian, 2 (28.6%) Southeast Asia (China), 1 (14.3%) Latin (mestizo) and 1 (14.3%) Arabic. They clinically presented as a malignant mammary neoplasia or as an infection. All radiologically demonstrated (mammography and ultrasound) as suspected malignant lesions and the diagnosis was made by histological examination after core needle biopsy guided by ultrasound. The first symptom was: 2 (28.6%) breast abscess, breast mass 4 (57.1%) and breast pain in one (14.3%). The lesion was located in 5 patients left breast and right breast in one. Predominated in upper quadrants. All patients underwent mammography and ultrasound findings of suspected malignancy and ultrasound-guided percutaneous biopsy gave the diagnosis. The evidence of autoimmunity and microbiological cultures were negative in all patients. All patients were treated with glucocorticoids at doses of 30 mg reduced the dough until its demise. Two patients required surgical drainage to start. No recurrences were observed Conclusions: IGM is a rare entity. Differential diagnoses should include malignant mammary neoplasia. The diagnosis is confirmed by pathologic examination. The treatment is medical with glucocorticoid. The prognosis of this disease remains favorable Disclosure of Interest: None declared